Fostering green investments and tackling climate-related financial risks: Which role for macroprudential policies? - Paola D'Orazio; Lilit Popoyan (Scuola Superiore Sant'Anna, Laboratory of Economics and Management (LEM), 2018)
While there is a growing debate among researchers and practitioners on the possible role of central banks and financial regulators in supporting a smooth transition to a low-carbon economy, the information on which macroprudential instruments could be used for reaching the "green structural change" is still quite limited. Moreover, the achievement of climate goals is still affected by the so-called "green finance gap". The paper addresses these issues by proposing a critical review of existing and novel prudential approaches to incentivizing the decarbonization of banks' balance sheets and align finance with sustainable growth and development objectives. The analysis carried out in the paper allows understanding under which conditions macroprudential policy could tackle climate change and promote green lending, while containing climate-related financial risks.
Keywords: 330; Climate Change; Climate Finance Gap; Banking Regulation; Macroprudential Policy; Central Banking; Climate-nance risk